Impact of midsole thickness on physiological responses during running in well-trained athletes - Gian-Andri Baumann; Mattia Nolé; Christina M. Spengler; Fernando G. Beltrami (Bern Open Publishing, 2024)
Introduction Modern running shoes have revolutionized long-distance performances by decreasing the amount of oxygen athletes need when running at a given speed, which is termed running economy. In 2022, World Athletics imposed an upper limit of 40 mm for midsole thickness, possibly to prevent shoes from having an overemphasized role in performance. This ceiling, however, seems arbitrary, and a better understanding of whether midsole thickness affects running economy is needed. This study therefore investigated if midsole thickness affects oxygen consumption both indoors and outdoors, as early findings from treadmill studies may not translate to overground running. Methods Following a familiarization trial including an incremental test, 16 well-trained male runners (weight 70 ± 6 kg, age 28 ± 5 years, peak oxygen uptake, V̇O2peak 64 ± 4 ml O2･kg-1･min-1, peak running speed 20.0 ± 0.8 km･h-1) completed two testing visits, once on a treadmill and once on a track, each consisting of twelve 5-min runs at submaximal speed (16 km･h-1) alternating three different footwear conditions: an entry-level running shoe (EL, 30 mm midsole thickness) and two carbon-plated modern running shoes with midsole thickness of 40 and 50 mm, respectively. The shoe order was randomized and balanced between each of the four replicates. Gas exchange and heart rate were continuously measured throughout the runs. Results Running with 40 mm shoes reduced V̇O2 compared with EL shoes by 2.4 ± 1.1% on the treadmill and 4.0 ± 1.2% when running overground (both p < 0.001). Running with 50mm shoes also decreased V̇O2 compared with EL shoes both on the treadmill (-2.7 ± 1.6%, p < 0.001) and overground (-4.6 ± 1.8%, p < 0.001), but no differences were detected between the modern shoes (40 mm vs. 50 mm treadmill: +0.3 ± 1.3%, p = 0.586; overground: +0.6 ± 1.4%, p = 0.189). Similarly, heart rate was lower compared with the EL shoes in both the 40 mm shoes (treadmill -1.3 ± 0.6%; overground -2.0 ± 0.6%; both p < 0.001) and 50 mm shoes (treadmill -1.6 ± 0.7%; overground -2.3 ± 0.6%, both p < 0.001), but no differences were detected between the modern shoes (40 mm vs. 50 mm treadmill: +0.3% ± 0.6%, p = 0.106; overground: +0.4 ± 0.6%, p = 0.090). Interestingly when running overground V̇O2 decreased over time for the 50 mm shoes, reaching significance between replicates 1 and 4 (p = 0.017), which was not the case for the 40 mm shoes (p = 0.817). The V̇O2 ratio between the 50 mm and 40 mm shoes was 1.003 in replicate 1 and 0.987 in replicate 4 (p = 0.108). Discussion/Conclusion Our data suggests that a 50 mm midsole does not offer significant benefits compared with race-legal 40 mm midsole shoes when tested over short durations. The 50 mm shoes cause a noticeable decrease in V̇O2 over time when used outdoors, which may reflect a learning effect to this unfamiliar midsole thickness. Longer test sessions may be necessary to reveal the actual impact on running economy of shoes with over 40 mm midsoles.